Food sources of the non-indigenous bivalve Ruditapes philippinarum (Adams and Reeve, 1850) and trophic niche overlap with native species Ester Dias1,*, - Dias, Ester (2019)
The Manila clam, Ruditapes philippinarum (Adams and Reeve, 1850), was introduced in many estuaries along the Atlantic and Mediterranean coasts for fisheries and aquaculture, being one of the top five most commercially valuable bivalve species worldwide. In Portugal, the colonization of the Tagus estuary by this species coincided with a significant decrease in abundance of the native R. decussatus (Linnaeus, 1758). This study aimed at identifying the main food sources supporting populations of the non-native bivalve in the Tagus estuary, using carbon and nitrogen stable isotopes, and evaluate the potential for food competition with the native bivalves R. decussatus and Cerastoderma glaucum (Bruguière, 1789). Results showed that these species relied on the same food sources, and that the trophic niche of R. philippinarum overlapped with the trophic niche of R. decussatus by 40% and with C. glaucum by 23%. The most likely food sources included particulate organic matter (POM), microphytobenthos (MPB), and sediment organic matter (SOM). The Bayesian stable isotope mixing model indicated that POM was the food source with the highest proportional contribution (up to 92%), followed by MPB (up to 32%), and SOM (up to 23%). Although the majority of the food sources identified were filtered from the water column, reliance on SOM and MPB suggests they may also feed on resuspended organic matter. Because these bivalve species feed on the same sources, there is some potential for food competition in this ecosystem. However, further studies are needed to analyze the long-term consequences of these trophic interactions to verify if the co-existence between the native and the invasive species will generate competition for food resources when those are limited in quantity and/or quality.